Social psychological dynamics of enhanced HIV risk reduction among peer interventionists - Dickson-Gomez, J.; Weeks, M.; Convey, M.; Li, Jianghong (2011)
The authors present a model of interactive social psychological and relational feedback processes leading to human immunodeficiency virus (HIV) risk reduction behavior change among active drug users trained as Peer Health Advocates (PHAs). The model is supported by data from qualitative interviews with PHAs and members of their drug-using networks in the Risk Avoidance Partnership (RAP) project. Results suggest three mutually reinforcing social psychological processes that motivate PHAs to provide HIV prevention intervention to their peers and to reduce their own risk behaviors: development of a prosocial identity, positive social reinforcement from drug users and community members, and cognitive dissonance associated with continued risk behavior while engaging in health advocacy. These processes directly influence peer interventionists' motivation and efficacy to continue giving intervention to their peers, and to reduce their HIV risk behaviors. The authors discuss implications of the model for continued research on effective HIV prevention in high-risk groups. © 2011 Wiley Periodicals, Inc.